Modeling the duration of return labor migration (by the example of kalmykia) - Eldyaeva, Nina A.; Galina A. Sharinova, Ekaterina S. Kovanova, Victoria M. Romadikova (Opción, 2019)
The article considers the process of internal labor migration in the Republic of Kalmykia and shows its econometric modeling. Econometric methods allow determining the nature and consequences of the influence of social and economic factors on migration. A set of socio-economic factors was identified that affect the duration of labor migration. Kalmykia is characterized by a large number of the outgoing population outside its region. To a large extent, the duration of labor migration depends on the age and level of education of labor migrants, as well as the amount of their income.